Harnessing the Potential of miRNAs in Malaria Diagnostic and Prevention - Gupta, Himanshu; Wassmer, Samuel C. (Frontiers in Cellular and Infection Microbiology, 2021)
Despite encouraging progress over the past decade, malaria remains a major global health challenge. Its severe form accounts for the majority of malaria-related deaths, and early diagnosis is key for a positive outcome. However, this is hindered by the non-specific symptoms caused by malaria, which often overlap with those of other viral, bacterial and parasitic infections. In addition, current tools are unable to detect the nature and degree of vital organ dysfunction associated with severe malaria, as complications develop silently until the effective treatment window is closed. It is therefore crucial to identify cheap and reliable early biomarkers of this wide-spectrum disease. microRNAs (miRNAs), a class of small non-coding RNAs, are rapidly released into the blood circulation upon physiological changes, including infection and organ damage. The present review details our current knowledge of miRNAs as biomarkers of specific organ dysfunction in patients with malaria, and both promising candidates identified by pre-clinical models and important knowledge gaps are highlighted for future evaluation in humans. miRNAs associated with infected vectors are also described, with a view to expandind this rapidly growing field of research to malaria transmission and surveillance.